Role of Clinical Pharmacist in Improving Medication Adherence and Monitoring Medicinal Plant–Drug Interactions in Heart Failure Patients - Khan, Muhammad Shafiq; Khan, Muhammad Zakryya; Amin, Farhana; Begum, Sania; Jogezai, Naqeeb Ullah; Iqbal, Zafar; Abdullah, Hafiz Muhammad; Uttra, Awais Ahmed (Biological and Clinical Sciences Research Journal, 2025)
Heart failure (HF) remains a leading cause of morbidity and mortality worldwide. Medication non-adherence and the concurrent use of medicinal plants increase the risk of adverse events and reduce therapeutic efficacy. Clinical pharmacists may play a critical role in optimizing adherence and monitoring herb–drug interactions. Objective: To evaluate the role of clinical pharmacists in improving medication adherence and tracking medicinal plant–drug interactions in HF patients. Methods: A prospective, controlled, interventional study was conducted from January 2023 to June 2024, including 230 adult patients with HF. Participants were randomized into intervention (pharmacist-led counseling and monitoring) and control (usual care) groups. Medication adherence was assessed using MMAS-8, and herb–drug interactions were monitored using standard databases over six months. Results: The intervention group showed significant improvement in adherence (MMAS-8: 6.32±1.12 to 7.85±0.70) compared to controls (6.28±1.15 to 6.50±1.05; p<0.001). Adverse events from interactions were lower (3.48% vs. 10.43%; p=0.03), and interaction resolution was higher in the intervention group (34.78% vs. 13.04%; p<0.001). Conclusion: Clinical pharmacist interventions significantly enhance medication adherence and reduce herb–drug–related risks in HF patients.